Destructive behaviors and organizational research : a comprehensive overview - Singh, Riann; Ramdeo, Shalini (Routledge, 2025)
"Destructive organizational behaviors including destructive leadership, abusive supervision, workplace bullying, sexual harassment in the workplace, workplace deviance, workplace incivility, workplace ostracism, social loafing, and workplace discrimination and injustice are explored in this book. These destructive organizational behaviors and negative perspectives have emerged as the most pervasive forms of mistreatment in today's workplace with the most costly and disastrous consequences across all levels: employees, teams, and organizations. This volume synthesizes and critically evaluates existing research and identifies future directions through research gaps on the most destructive organizational behaviors in today's workplace. Strategies for managing such behaviors and potential contextual variations in destructive behaviors are also assessed. Alternative negative perspectives on traditionally positive organizational behaviors are examined. There is a paucity of research on the darker side of organizational behaviors, although such destructive behaviors are indeed pervasive in today's workplace. Providing researchers with a comprehensive overview and analysis of research advances on selected destructive organizational behaviors, this book also considers the need of researchers to delineate future research opportunities to advance the field of study. It seeks to spur critical thinking, spark alternative research perspectives, and provide the foundation from which focused future research can develop. It also considers managerial and international perspectives through an assessment of strategies for managing destructive behaviors and contextual reflections on destructive organizational behaviors, making it a valuable resource for researchers, academics, and students in the fields of organizational behavior, psychology, management, leadership, and strategy"-- Provided by publisher.
Keywords: Organizational behavior.; Psychology, Industrial.; Problem employees.; Discrimination in employment.; Personnel management.; elektronické knihy; electronic books